The association between systemic inflammatory response index and contrast-associated acute kidney injury in patients undergoing elective percutaneous coronary intervention - Jun-Han Chen; Li-Wei Zhang; Wen-Jia Liang; Wei-ze Lin; Xiao-Fang Chen; Zhi-Jie Lin; Chang-Xi Wang; Kai-Yang Lin; Yan-Song Guo (Renal Failure)
Background The systemic inflammatory response index (SIRI), served as a novel inflammatory biomarker, is the synthesis of neutrophils, monocytes and lymphocytes.Aims We hypothesized that SIRI has predictive value for contrast-associated acute kidney injury (CA-AKI) and long-term mortality in patients undergoing elective percutaneous coronary intervention (PCI).Methods We retrospectively observed 5685 patients undergoing elective PCI from January 2012 to December 2018. Venous blood samples were collected to obtain the experimental data on the day of admission or the morning of the next day. SIRI = neutrophil count × monocyte count/lymphocyte count. CA-AKI was defined as an increase of 50% or 0.3 mg/dl in SCr from baseline within 48 h after contrast exposure.Results The incidence of CA-AKI was 6.1% (n = 352). The best cutoff value of SIRI for predicting CA-AKI was 1.39, with a sensitivity of 52.3% and a specificity of 67.3%. [AUC: 0.620, 95% confidence interval (CI): 0.590–0.651, p < 0.001]. After adjusting for potential confounders, multivariate analysis showed that the high SIRI group (SIRI > 1.39) was a strong independent predictor of CA-AKI in patients undergoing elective PCI compared with the low SIRI group (SIRI ≤ 1.39) (odds ratio = 1.642, 95% CI: 1.274–2.116, p < 0.001). Additionally, COX regression analysis showed that SIRI > 1.39 was significantly associated with long-term mortality at a median follow-up of 2.8 years. [Hazard ratio (HR)=1.448, 95%CI: 1.188–1.765; p < 0.001]. Besides, Kaplan–Meier survival curve also indicated that the cumulative rate of mortality was considerably higher in the high SIRI group.Conclusions High levels of SIRI are independent predictors of CA-AKI and long-term mortality in patients undergoing elective PCI.